Evaluation Cytotoxic Effect of Nostoc sp. and Scenedesmus acuminatus Extracts on Cell Line Hep -2 in vitro - Al-Rubaiee, Ghaidaa; Dwaish, Ahmed (Iraqi Journal of Science, 2023)
In this Study, isolate and identification two types of algae Scenedesmus acuminatus (Lag.) Chodat belonging to Division of green –algae and Nostoc sp. Of the belong to Division of cyanobacteria from fountain pool at the University of Al- Mustansiriya. Use culture medium Chu- 10 for growth of algae on batch culture in the laboratory conditions (25 ˚ c ±2 and light intensity 200 μE/m²/sec the light:dark regime was used 16:8 hrs). Harvested culture after fourteen days of age farm. Use methanol 95% to extract active compound from raw dry biomass, Tested the effectiveness of the efficiency of the cell extract toward the cell line (human larynx cancer) Hep-2 from biotechnology center at the University of Alnahrain university and different concentrations (125, 250, 500, 1000, 2000 and 4000 μg / mL) The study showed that the extract of green algae Scenedesmus acuminatus better the effectiveness of the extract blue green alga Nostoc sp. toward the cell line Hep -2 found that the extract has a toxic effect of all concentrations had a higher effectHigher toxic effect of the extract at concentration Senedesmus acuminatus 1000 μg / mL by 69.19%, while the toxic effect was higher when the concentration 4000 μg / mL by 55.4% to blue-green alga extract Nostoc sp. Did not show inhibitory effect at concentrations of a few under study.